Zeolite/aluminum composite adsorbents for application in adsorption refrigeration - Bauer, J.; Herrmann, R.; Mittelbach, W.; Schwieger, Wilhelm; et al. (International Journal of Energy Research, 2009)
Thermally driven adsorption refrigerators, which transform available low-temperature waste heat (from processes, engines, solar radiation, district heat) into useful cooling energy, are a very promising and green technology to reduce the demand for primary energy. To improve their refrigeration performance, new zeolite/aluminum composite adsorbents with optimized sorption and heat transfer properties were prepared following the partial support transformation technique. A direct and binderless contact between the closed zeolite layer and the metal could be established which enables best thermal diffusivity. It is shown by measurements of thermal sorption capacities and kinetics on planar samples and on coated heat exchangers that this causes best sorption performance combined with high mechanical stability.
EAM Import::2019-03-12